A study of speculation activities towards the high price of housing in Kota Kinabalu / Rosnilah M. Fathil Ibrahim - M. Fathil Ibrahim, Rosnilah (2015)
The main purpose of this study is to examine the government policies that affecting the housing price in Kota Kinabalu. Secondly, is to examine factors towards population growth in Kota Kinabalu and thirdly is identify housing developer attitudes towards the price in Kota Kinabalu. This paper examines empirically whether the increasing trend in the housing price is related to changes in government policies, population, costs of construction, interest rate and Real Property Gains Tax (RPGT). The paper is exploratory in nature. The empirical data were collected from the general public which consisted of government staffs, banks staffs and private sector staffs in Kota Kinabalu. The paper provides empirical results that the government policies, population and RPGT are the key determinants of housing prices. However, changes in housing prices may not necessarily be influenced by the government policies, population and RPGT in Kota Kinabalu.